Development and testing of a soot particle concentration estimator using Lagrangian post-processing. Issue 1 (1st January 2018) - Alexander, Raymond; Bozorgzadeh, Sepehr; Khosousi, Ali; Dworkin, Seth B.
ABSTRACT: Soot emissions from combustion devices are known to have harmful effects on the environment and human health. As the transportation industry continues to expand, the development of techniques to reduce soot emissions remains a significant goal of researchers and industry. In order for current soot modeling techniques to be reliably accurate, they must incur an intractably high computational cost. This project leverages existing knowledge in soot modeling and soot formation fundamentals to develop a stand-alone, computationally inexpensive soot concentration estimator to be linked to Computational Fluid Dynamics simulations as a post-processor. Preliminary development and testing of the estimator is presented here for laminar flames. As soot properties cannot be determined by local conditions, the estimator consists of a library generated using the hystereses of soot-containing fluid parcels, which relates soot concentration to the aggregated gas-phase environment histories to which a fluid parcel has been exposed. The estimator can be used to relate soot concentration to computed parcel hystereses through interpolation techniques. The estimator shows the potential ability to produce accurate results with very low computational cost in laminar coflow diffusion flames. Results also show that as flame data representing a broader set of conditions (temperature, mixture fraction, residence time, etc.) are added to the library, the estimator becomes applicable to a wider range of flames.